Triboelectrostatic separation of polypropylene, polyurethane, and polyvinylchloride used in passenger vehicles. (March 2018) - Li, Tuyu; Yu, Dali; Zhang, Hongshen
Highlights: In the article, a high-voltage triboelectrostatic sorting device was developed to separate PP, PU and PVC in a discarded vehices plastic mixture. Products of PP, PU, and PVC were obtained after two-stage separation; their purity exceeded 95%, and their productivities were 74%, 94%, and 41%, respectively. The appropriate experimental parameters for high voltage level, rotational speed of the friction drum and cylinder electrode for the first and the second stage of separation were gained respectively. Results showed that hybrid materials should be selected based on the triboelectric series to separate three-component plastic mixtures feasibly. Abstract: Recycling and reuse of automotive plastics have elicited global attention due to the increasing number of end-of-life vehicles. Through the single-factor experiment, a high-voltage triboelectrostatic sorting device was developed to separate polypropylene (PP), polyurethane (PU), and polyvinylchloride (PVC) in a plastic mixture commonly used in exterior and interior parts of passenger vehicles. Products of PP, PU, and PVC were obtained after two-stage separation; their purity exceeded 95%, and their productivities were 74%, 94%, and 41%, respectively. The appropriate experimental parameters for high voltage level and rotational speed of the friction drum and cylinder electrode for the first stage of separation were 35 kV, 30 rpm, and 35 rpm, respectively, and the parameters for the second stage of separation were 35 kV, 30 rpm, and 25 rpm, respectively. Results showed that hybrid materials should be selected based on the triboelectric series to separate three-component plastic mixtures feasibly.